Level of Knowledge and Understanding of State Senior High School Science Teachers in Constructing â€œHOT Questionsâ€ - Rahmati Rahmati; Yusrizal Yusrizal; A Halim; Fitria Herliana; Syamsul Rizal (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to describe the level of knowledge and understanding of state senior high school science teachers (SMAN) in constructing higher-order thinking items (HOT), and to compar e the level of knowledge and understanding among state senior high school Physics, Chemistry, and Biology teachers in constructing higher-order thinking items (HOT). The type of this research is descriptive quantitative, data collection technique is done by survey method using developed questionnaire instrument. The population in this research are all science teachers (Physics, Chemistry, and Biology) of State Senior High School teachers in Aceh Province, with the sample being 90 science teachers of State Senior High School teachers which are chosen randomly. The data obtained were analyzed descriptively. The result of the research shows that: (1) the level of knowledge and understanding of science teachers of State Senior High School teachers in constructing higher-order thinking items (HOT) is in the medium category, (2) the level of knowledge and understanding in constructing higher-order thinking (HOT) items, Biology teachers achieved more high and very high category compared to Physics and Chemistry teachers.